Penguatan Identitas Nasional Melalui Transformasi Masyarakat Adat Berbasis Civic Empowerment - Mulyati, Tita; Nanggala, Agil; Rahmadiyani, Alya; Dewi, Dinie Anggraeni; Aljamaliah, S Nailul Muna; Arifin, Muh Husen (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
The strengthening of national identity within the context of indigenous communities continues to face challenges due to the dynamics of globalisation, which affect the sustainability of cultural values and community life. This study aims to analyse the transformation of indigenous communities based on civic empowerment and its role in strengthening national identity in Tajur Village, Purwakarta Regency. The study employs a qualitative approach using grounded theory, which is oriented towards the development of a model based on empirical data. Data were collected through interviews with community leaders, government officials, young people and experts, field observations, and a review of relevant documentation. Data analysis was conducted through the stages of data condensation, data presentation and verification, with data validity reinforced through triangulation and focus group discussions. The research findings indicate that the transformation of indigenous communities based on civic empowerment is realised through the wise and sustainable integration of local wisdom, modernisation, and digital technology. This transformation demonstrates a strengthening of national identity, characterised by cultural preservation, the development of a creative economy based on handicrafts, and the management of tourism based on ecotourism. The active involvement of communities in various social, economic and cultural activities demonstrates that indigenous communities have the capacity to act as agents of transformative development. Research findings confirm that the transformation of indigenous communities through civic empowerment is a relevant approach to strengthening national identity through adaptive, innovative and sustainable community empowerment.